FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR GAMBIR INDONESIA KE PASAR INDIA - Anhary, Febri; Leovita, Angelia; Fauzi, Dian (JURNAL AGRIMANSION, 2025)
Gambir (Uncaria Gambir Roxb) is one of Indonesia's leading export commodities that has various benefits, especially in the health and pharmaceutical industries. Indonesia is the largest gambir exporting country in the world. Indonesia exports the most gambir to India. The average volume of gambir exports is smaller than the production of gambir in Indonesia, there is a difference of 275.64 tons. This excess production should be able to be exported again to be used as an additional foreign exchange earner. The objectives of this study are 1) to analyze the factors that influence the volume of Indonesian gambir exports to India 2) to analyze trends or forecasts of gambir export volumes. This study uses time series data from 2003-2023 and forecasts of export volumes from 2024-2033. This study uses multiple linear regression analysis and trend analysis (forecasting). The results of the study are that the factors that influence the volume of gambir exports are production, export prices and Indian consumption, while the rupiah exchange rate variable does not affect the volume of gambir exports. Gambir forecast for the next 10 years produces 25,978,578 tons in 2033.